Modified Mason-Allen with Mattress Sutures and Double Row Suture Bridge in Musculotendinosis Rotator Cuff Tear - Renaldi Prasetia, M.D., M.Med.Sc., Ph.D.; Siti Zainab Bani Purwana, M.D.; Greesea Dinamaria, M.D.; Hermawan Nagar Rasyid, M.D., Ph.D.; Agus Hadian Rahim, M.D., M.Sc. (Arthroscopy Techniques)
Musculotendinous rotator cuff tear is rarely encountered, and the repair is challenging with high retear rate. There is no definitive guideline on how to manage the tear. We present step-by-step the modified Mason-Allen technique using horizontal mattress sutures and double-row suture bridge for musculotendinous rotator cuff tear repair, which is simple to implement and improves soft-tissue stability while avoiding tendon constriction.